2 Mapping of bereavement services across the north east of england – a survey of general practitioners referring practice. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Wakefield, D; Dewhurst, F; Brown, J; Kavanagh, E; Kiltie, R; McCormick, F; Pickard, J; Rowley, G; Waterfield, K; Woods, L; Clark, A
Abstract : Background: Recent national guidelines have identified the importance of bereavement support. However, evidence suggests that bereavement services are provided inconsistently. We aimed to map bereavement services used by GPs across the North-East-of-England to identify inequalities. Method: An electronic bereavement service questionnaire was produced through consultation with Northern England Clinical Networks and CCG end-of-life-care leads and was then reviewed by a local GP focus group. The questionnaire was then distributed to CCG EOLC leads who cascaded it to all 392 practices in the North-east of England. A Reminder email was sent after 4 weeks. Results: 85 (22%) GP practices completed the survey. Only 43.5% and 9.4% of practices reported that they had a bereavement policy and that the majority of their GPs' had had bereavement training respectively. 21% reported that they would not refer patients anywhere for bereavement support. The remaining 79% listed 18 services that they refer to, most commonly; hospices(21%), CRUSE(17%), MIND(15%), Macmillan(10%) and their own in-house counsellor(10%) and 25 services that they recommend for self-referral, CRUSE(65%), talking therapy(16%), hospice(14%), Improved Access to Psychological Therapies(11%). Conclusion: A wide range of bereavement services are used across the region. They mainly depended on charitable funding. One fifth of responding GP practices reported that they would not refer patients for bereavement support. This was associated with comments including 'local services have been decommissioned' and 'not aware of any services to refer to'. This highlights the wide variation in use and availability of bereavement services across the region, and the problems of service withdrawal, lack of funding and lack of clarity on who is responsible for bereavement support. This will be invaluable in providing evidence to commission future bereavement services.